Prevalence of neurological manifestations in coronavirus disease 2019 positive patients in Makkah city – Saudi Arabia - Eyad Altarazi; Amal M AlKhotani; Doaa Khalid Mohorjy; Abdullah Almoabdi; Rahaf Almatrafi (Saudi Journal for Health Sciences, 2023)
Background: Coronaviruses are the important pathogens of humans and animals that can cause diseases ranging from the common cold to more severe or even fatal respiratory infections. Regarding nervous system complications, existing literature has revealed increasing reports of neurological manifestations in coronavirus disease 2019 (COVID-19)-positive patients ranging from mild-to-severe manifestations. Aim: In this study, we aimed to determine the prevalence of neurological manifestations in COVID-19-positive patients. Furthermore, we sought to ascertain the most common and most severe manifestations and to find the significant associations with laboratory or clinical findings. Setting and Design: This is a retrospective cross-sectional observational study that was conducted at two centers. Materials and Methods: Patient data were collected in periods from of March 1 to of July 30, 2020 labeled as the first wave, and from December 1, 2021 to January 30, 2022 labeled as the second wave in two tertiary care hospitals, Al-Noor Specialist Hospital and King Abdullah Medical City, situated in Makkah city, Saudi Arabia. The study included patients who were ≥ 18 years of age and were found to have any neurological manifestations and/or complications secondary to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. The study was conducted in different periods to assess the different waves of the COVID-19 pandemic and to allow the comparison between them. Results: From a total number of 4751 patients with confirmed SARS-CoV-2 infection eligible during the periods included in our study, we found neurological manifestations in 263 patients, particularly 229 from the first wave and 34 from the second wave. In the first wave patients, 102 (44.5%) were aged between 18 and 39 years of age. The prevalence of neurological manifestations was 6.4% in the first wave and 2.9% in the second wave. Conclusion: Our study showed a large variety of neurological manifestations in COVID-19-positive patients. The most common neurological manifestations were headache and impaired level of consciousness, whereas the most severe conditions were cerebrovascular events, seizure, encephalopathy, and brain death.